Enhancement of the photocurrent and efficiency of CdTe solar cells suppressing the front contact reflection using a highly-resistive ZnO buffer layer - Giray Kartopu (Solar Energy Materials and Solar Cells, 2019)
We report on the effects of using an atomic layer deposited ZnO transparent buffer layer with > 106 Ω cm resistivity on the performance of CdZnS/CdTe solar cells grown by metalorganic chemical vapour deposition (MOCVD). The buffer film thickness is adjusted by optical modelling to suppress the reflection losses at the front contact. A clear improvement, up to 1.8% in conversion efficiency, was obtained in comparison to reference devices without the ZnO buffer layer, thanks to the enhancement of the current density (Jsc) and fill factor (FF). Device spectral response showed improved collection for most of the visible region. Reflectance measurements confirmed that the ZnO film reduced the optical reflectance around the transparent front contact. This effect permitted light management through the front contact leading to an improvement of the Jsc and hence the photovoltaic conversion efficiency. These results are intriguing since the literature on CdTe solar cells did not previously report improvement to the photocurrent and device response through controlling the highly-resistive transparent buffer layer.